2021
DOI: 10.18295/squmj.2021.21.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Efficacy and Social Support after an Intervention to Increase Physical Activity Among Adults with Type 2 Diabetes in Oman

Abstract: Objectives: This study aimed to describe changes in self-efficacy (SE) and social support (SS) 12 months after the MOVEdiabetes trial, an intervention designed to increase physical activity (PA) among adults with type 2 diabetes mellitus in Oman. Methods: The original MOVEdiabetes trial was conducted between April 2016 and June 2017 in Muscat, Oman. The intervention group (IG) received personalised PA consultations, pedometers and monthly messages using a web-based application, while the comparison group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…As baseline self-efficacy appears to be an important predictor of physical activity, the importance of support to improve self-efficacy at the beginning of an intervention is emphasised. It has been shown that walking interventions with lengths ranging from eight weeks [40] up to 12 months [41] can improve self-efficacy levels. However, self-efficacy often acts as a mediator between the exposure (e.g., the intervention) and the outcome (e.g., physical activity) [42].…”
Section: Discussionmentioning
confidence: 99%
“…As baseline self-efficacy appears to be an important predictor of physical activity, the importance of support to improve self-efficacy at the beginning of an intervention is emphasised. It has been shown that walking interventions with lengths ranging from eight weeks [40] up to 12 months [41] can improve self-efficacy levels. However, self-efficacy often acts as a mediator between the exposure (e.g., the intervention) and the outcome (e.g., physical activity) [42].…”
Section: Discussionmentioning
confidence: 99%
“…Scales to measure social support for diet and exercise behaviors: The internal consistency was described in the five studies that tested this scale [23,93,[95][96][97]. Three studies were rated as sufficient [93,96,97] and the remaining two studies were rated as insufficient as the reported Cronbach's values were < 0.70 [23,95]. The construct validity was reported in one study [23] and it was scored as insufficient (correlations' values < 0.30).…”
Section: Quality Of Psychometric Properties Of Instrumentsmentioning
confidence: 99%